2018
DOI: 10.1016/j.materresbull.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Computational and experimental analysis on Te-doped ZnSb thermoelectric material

Abstract: In this study we report a combined theoretical and experimental work on the tellurium doping of thermoelectric ZnSb. We investigated the influence of tellurium on the phase's stabilities by density functional theory (DFT) calculations. During experimental validation by means of SEM and EPMA characterization "needlelike" areas of Te-doped ZnSb were identified. The experimental results also highlight that for the compositions Zn 0.5 Sb 0.5-x Te x (x=0.001, 0.05, 0.1) the system reaches a non-equilibrium state wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This method is simple, but it does not take into consideration the phases which are in equilibrium with the compound containing defects [ 4 , 29 ]. To correct this, two methodologies can be used.…”
Section: Determination Of the Energy Of Formation Of Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is simple, but it does not take into consideration the phases which are in equilibrium with the compound containing defects [ 4 , 29 ]. To correct this, two methodologies can be used.…”
Section: Determination Of the Energy Of Formation Of Defectsmentioning
confidence: 99%
“…To avoid the limitations of the two previous formalisms, it is possible to modify Equation (4) by replacing the Δ f E(pure) by the Δ f E(multi) as suggested in our previous works [ 4 , 29 ]. In this third formalism, we assume that the defect will change the global composition of the alloy.…”
Section: Determination Of the Energy Of Formation Of Defectsmentioning
confidence: 99%
“…For thermoelectric applications, the full Heusler Fe2VAl compound may be a good challenger to conventional bismuth telluride (Bi2Te3) currently used in commercialized thermoelectric refrigerators. Most of the thermoelectric materials are small-gap semiconductors doped to obtain optimal carrier concentrations (around 10 19 charges.cm -3 ) which generally allow to have materials with a high figure-of-merit (named ZT = S 2 σT/ where T is the temperature, S the Seebeck coefficient, σ and  the electrical and thermal conductivity respectively). Fe2VAl exhibits a ZT max around 0.3 at 500K for Tantalum-doped bulk materials [1].…”
mentioning
confidence: 99%
“…below the L21/B2 transition temperature (1353K)), partial disorder is observed due to inversions between Al and V atoms. In the spirit of our previous works on point defects in thermoelectric materials such as NiTiSn [14][15][16], NiHfSn [17], NiZrSn [18] and ZnSb [19][20], we here investigate the impact of temperature and partial disorder in the stoichiometric Fe2VAl through first-principles DFT calculations. The effect of off-stoichiometric defects has been discussed in a previous work [11].…”
mentioning
confidence: 99%
“…We used the same calculation method as Zhao et al 50 to obtain a maximum ZT value of 1.6 for SnS 0.91 Se 0.09 , and analyzed it experimentally. Pothin et al 51 analyzed Te-doped ZnSb materials with a computational method, and demonstrated the rationality of the calculated results through experiment. S. Sharma et al 52 verified the excellent thermoelectric performance of Bi 2 Te 3 material through theoretical calculation, and later Wang et al 53 successfully verified the excellent thermoelectric performance of the Bi 2 Te 3 material in experiments.…”
Section: Introductionmentioning
confidence: 98%